THE The Effect Of Ring Frame Thread Number And Winding Machine Counter On The Weight Of 69G Lot Cones On Winding Machine Number 8 - Pravitasari, Filly; Kusumadewi, Afriani; Nurherawaty, Feny; Sulistio, Rino (Universitas Insan Cendekia Mandiri, 2024)
Abstract: A good and appropriate product quality control system can maintain product quality in accordance with the standards set by the company. Fabrics produced at PT X still has problems, namely the existence of product defects that exceed the maximum tolerance limit for defective products that have been set by the company, which is 2%. Types of fabric defects that often occur include color not ok (WTO), spot defects, crease marks and dirty color, so it is necessary to do an analysis for product quality control in each process using statistical quality control methods. ). Statistical quality control can detect the existence of special causes in variations or process errors through analysis of data from the past and the future by finding the cause of damage or product defects through existing data. Based on the results of the p control chart (p-chart) it was found that the quality of 100% viscose rayon fabric was outside the control limit, it was shown that there were still points that were outside the control limit and these points fluctuated very high and irregularly. This is an indication that the process is in an uncontrolled state or is still experiencing deviations. Furthermore, the results of the causal diagram analysis can identify the factors that cause defects in the production process, which are derived from factors of workers, production machines, work methods, and dyestuff/material. The data from the statistical quality control results can be quickly corrected so that the same mistakes do not happen again. Keywords : Quality Control, Fabric Defects, fishbone diagram